Germ Cell Tumors Overexpress the Candidate Therapeutic target Cyclin B1 Independently of p53 function. Issue 3 (July 2015) - De Giorgi, Ugo; Yuan, Juping; Moroni, Mauro; Veronese, Silvio; Sartore-Bianchi, Andrea; Broggini, Massimo; Rosti, Giovanni; Strebhardt, Klaus; Ruffini, Pier Adelchi
Germ cell tumors (GCTs) generally express wild-type p53 protein. Rare p53 mutations may be associated with cisplatin resistance. There is growing interest in the role of cyclins as targets for GCTs. Cyclin B1 is involved in G2/M transition and its overexpression has been reported in tumors carrying nonfunctional p53. Conversely, cyclin B1-specific small interfering RNAs have been shown to dramatically reduce tumor proliferation. We investigated whether a subset of chemotherapy-resistant GCTs overexpressed cyclin B1 as a result of nonfunctional p53, as this would make cyclin B1 a potential therapeutic target. Our data showed that GCTs consistently overexpressed cyclin B1 independently of their responsiveness to chemotherapy or the presence of p53 mutations. Cyclin B1 was overexpressed by GCT cell lines carrying functional p53. Cyclin B1-specific small interfering RNAs only slightly reduced the proliferation of JAR and JEG-3 placental choriocarcinoma cells. Further research into targeting cyclin B1 could provide a novel intervention for GCTs.